PENCAPAIAN TARGET KUNJUNGAN PEMUSTAKA MELALUI BELANJA MODAL KOLEKSI PERPUSTAKAAN (Studi di Perpustakaan Umum Kota Pekalongan Periode 2010 â 2013) - Junaenah, 1242020062 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study to determine how much capital expenditure to be able to increase the optimal library visitors bidget based on existing libraries in Pekalongan City Public Library.This type of research is quantitative descriptive. research study conducted to illustrate the extent of capital expenditures libraray collection give effect to an increase the library visitors. The data used in study is secondary data ini Public Library in Pekalongan City. The analysis tool used elasticity, to measure the degree of elasticity increase capital expenditure libraray collection to rise library visitors.The results showed that the increase capital expenditure libraray collection affecting to rise library visitors. This can be seen from the value of the elasticity of 4,2 means that every 4,2 percent increase in capital expenditure library collection affecting 1 percent of library visitors. Keywords: capital expenditures library collection, level ofÂ library visitors.